2014
DOI: 10.1016/j.jbtep.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A pilot validation of a modified Illness Perceptions Questionnaire designed to predict response to cognitive therapy for psychosis

Abstract: Background and objectivesClinical responsiveness to cognitive behavioural therapy for psychosis (CBTp) varies. Recent research has demonstrated that illness perceptions predict active engagement in therapy, and, thereby, better outcomes. In this study, we aimed to investigate the psychometric properties of a modification of the Illness Perceptions Questionnaire (M-IPQ) designed to predict response following CBTp.MethodsFifty-six participants with persistent, distressing delusions completed the M-IPQ; forty bef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…Therapy expectations emerged as the strongest correlates of satisfaction, demonstrating associations with both overall satisfaction and perceptions of progress, skills, and understanding gained from therapy. Expectations of therapy have been a neglected area of research, but there is an emerging literature suggesting that expectations of therapy may be linked to the process and outcome of therapy in CBTp (e.g., Freeman et al ., ; Holding et al ., ; Marcus et al ., ). For example, individuals with psychosis who perceive that their problems can change, and that their own efforts or therapy may contribute to this, have been found to be more likely to engage with CBTp sessions and to experience greater progress (Freeman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Therapy expectations emerged as the strongest correlates of satisfaction, demonstrating associations with both overall satisfaction and perceptions of progress, skills, and understanding gained from therapy. Expectations of therapy have been a neglected area of research, but there is an emerging literature suggesting that expectations of therapy may be linked to the process and outcome of therapy in CBTp (e.g., Freeman et al ., ; Holding et al ., ; Marcus et al ., ). For example, individuals with psychosis who perceive that their problems can change, and that their own efforts or therapy may contribute to this, have been found to be more likely to engage with CBTp sessions and to experience greater progress (Freeman et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Our previous proof-of-concept experiment suggested that working memory and negative symptoms moderated effects of the intervention on reasoning ( Garety et al., 2014 ). We also know that beliefs about the causes and treatability of one's problems and the relevance of psychological treatment may affect engagement, and consequently outcome ( Freeman, Dunn, Garety, et al, 2013 ; Marcus et al., 2014 ). An important goal of future research is to clarify the reasons for treatment engagement and treatment effect heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…The Illness Perceptions Questionnaire (IPQ) has also been modified several times for use in those with psychosis (Lobban, Barrowclough, & Jones, ; Marcus et al ., ; Watson et al ., ). Although the modified IPQ shares some similar content with the PBIllQ and PBEQ, both considering causes and control over experiences, there are also some notable differences.…”
Section: Discussionmentioning
confidence: 99%